New Cyber Physical System Challenges for Human-in-the-Loop Control - Munir, Sirajum; Stankovic, John A.; Liang, Chieh-Jan Mike; Lin, Shan (Feedback Computing (International Workshop on Feedback Computing), 2013)
This paper articulates three main challenges for employing feedback control with humans in the loop. They are: (i) the need for a comprehensive understanding of the complete spectrum of the types of human-in-the-loop controls, (ii) the need for extensions to system identification or other techniques to derive models of human behaviors, and (iii) most importantly, determining how to incorporate human behavior models into the formal methodology of feedback control.